EprS, an autotransporter protein of Pseudomonas aeruginosa, possessing serine protease activity induces inflammatory responses through protease‐activated receptors. (28th January 2013) - Kida, Yutaka; Taira, Junichi; Yamamoto, Takeshi; Higashimoto, Yuichiro; Kuwano, Koichi
Summary PA3535 (EprS), an autotransporter (AT) protein of Pseudomonas aeruginosa, is predicted to contain a serine protease motif. The eprS encodes a 104.5 kDa protein with a 30‐amino‐acid‐long signal peptide, a 51.2 kDa amino‐terminal secreted passenger domain and a 50.1 kDa carboxyl‐terminal outer membrane channel formed translocator. Although the majority of AT proteins have been reported to be virulence factors, little is known about the functions of EprS in the pathogenicity of P. aeruginosa. In this study, we performed functional analyses of recombinant EprS secreted by Escherichia coli. The proteolytic activity of EprS was markedly decreased by changing Ser to Ala at position 308 or by serine protease inhibitors. EprS preferred to cleave substrates that terminated with arginine or lysine residues. Thus, these results indicate that EprS, a serine protease, displays the substrate specificity, cleaving after basic residues. We demonstrated that EprS activates NF‐κB‐driven promoters through protease‐activated receptor (PAR)‐1, ‐2 or ‐4 and induces IL‐8 production through PAR‐2 in a human bronchiole epithelial cell line. Moreover, EprS cleaved the peptides corresponding to the tethered ligand region of PAR‐1, ‐2 and ‐4 at a specific site with exposure oftheir tethered ligands. Collectively, these results suggest that EprS activates host inflammatory responses through PARs.